The Cardiac Pacemaker Story—Fundamental Role of the Na+/Ca2+ Exchanger in Spontaneous Automaticity - Kohajda, Zsófia; Loewe, Axel; Tóth, Noémi; Varró, András; Nagy, Norbert (Frontiers in Pharmacology, 2020)
The electrophysiological mechanism of the sinus-node automaticity was considered exclusively to the function of the so-called „funny-current” for a long time, however, parallel investigations increasingly emphasized the importance of the Ca2+-homeostasis and Na+/Ca2+ exchanger. Recently, large number of experimental evidences, as well as delicate mechanistic in-silico modeling demonstrate the crucial role of the exchanger in sinus-node pacemaking. This review aimed to focus to the emerging role of Na+/Ca2+ exchanger from the early results to the recent concepts.